2020
DOI: 10.1038/s41598-020-74792-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analysis of the expression and prognostic value of chromobox family proteins in human breast cancer

Abstract: Chromobox (CBX) family proteins control chromatin structure and gene expression. However, the functions of CBXs in cancer progression, especially breast cancer, are inadequately studied. We assessed the significance of eight CBX proteins in breast cancer. We performed immunohistochemistry and bioinformatic analysis of data from Oncomine, GEPIA Dataset, bcGenExMiner, Kaplan–Meier Plotter, and cBioPortal. We compared mRNA and protein expression levels of eight CBX proteins between breast tumor and normal tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
(53 reference statements)
0
27
0
Order By: Relevance
“…Downregulated expression levels in cancer tissues have consistently been reported for SENP2 [52][53][54][55][56][57] and PIAS2 [58][59][60]. The prognostic value of a single SUMO machinery component can also vary between cancer (sub)types, and, e.g., the value for PC2 [61,62] and PIAS4 [63,64] as prognostic biomarkers in breast cancer and for PIAS3 [65,66] in mesothelioma remains ambiguous (Table 1). Bioinformatic analyses of the SUMO machinery protein and mRNA levels, and their association with prognosis, utilizing datasets from various databases are generally well in line with the other published analyses of often smaller sample sizes [67][68][69] (and Supplementary Table S1).…”
Section: Altered Expression and Prognostic Significance Of Sumo Pathway In Cancermentioning
confidence: 99%
“…Downregulated expression levels in cancer tissues have consistently been reported for SENP2 [52][53][54][55][56][57] and PIAS2 [58][59][60]. The prognostic value of a single SUMO machinery component can also vary between cancer (sub)types, and, e.g., the value for PC2 [61,62] and PIAS4 [63,64] as prognostic biomarkers in breast cancer and for PIAS3 [65,66] in mesothelioma remains ambiguous (Table 1). Bioinformatic analyses of the SUMO machinery protein and mRNA levels, and their association with prognosis, utilizing datasets from various databases are generally well in line with the other published analyses of often smaller sample sizes [67][68][69] (and Supplementary Table S1).…”
Section: Altered Expression and Prognostic Significance Of Sumo Pathway In Cancermentioning
confidence: 99%
“…The CBX family of genes is thought to represent vital elements in a variety of tumors (14)(15)(16). However, the association between CBXs and sarcoma has not been extensively reported.…”
Section: Discussionmentioning
confidence: 99%
“…found that HP1- α/β/γ (CBX1/3/5) and CBX2/4/6/7 exerted an effect on breast cancer, thus indicating that CBX2 is expressed at high levels in basal-like and HER-2 subtypes ( 14 ). In addition, CBX4/7 is highly expressed in Luminal A and Luminal B subtypes of breast cancer ( 14 , 15 ). The increased mRNA expression of HP1- β/γ (CBX1/3) and CBX2 has been linked to a poorer Relapse free survival (RFS) via survival analysis; better outcomes were found to be associated with higher expression levels of CBX4/5/6/7 ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chromobox (CBX) family proteins are canonical components of polycomb group (PcG) complexes, which contain a single N-terminal chromodomain [7,8]. The CBX family of proteins is reported to be involved in various biological processes, such as cell cycle regulation, cell cycle regulation, gene expression, and tumor initiation.…”
Section: Introductionmentioning
confidence: 99%